Subsídios de um projeto híbrido internacional para o ensino de inglês na tecnologia de gestão empresarial: cenários verossímeis - Succi Junior, Osvaldo (2017)
Technological advancements drive the growth of online interactions to carry out activities that require the collaboration of participants. Both in business transactions and in academic situations, groups of collaborators strive to find hybrid solutions that integrate face-to-face and at distance activities. After participating in two virtual exchanges (VE) between two higher education institutions, a Brazilian and an American one, I decided to focus this study on some aspects present in the interactions between professors and students from both institutions. My expectation was that these evidences, aligned with a process of self-reflection, could serve as a contribution for professors of English language disciplines, not only in Business Management programs, but also in other similar programs in different Brazilian institutions. The VE under analysis was developed by a team of professors from both institutions and involved a series of online activities for groups of students to discuss the process of introducing a product or service in either the Brazilian or the American market. These activities were utilized as evidence to analyze cultural and linguistic aspects in exchanges like this. In theoretical terms, I used the Multiliteracies approach (NEW LONDON GROUP, 1996; COPE & KALANTZIS, 2017) and the Case Study (GIL, 2002; PIMENTA, 2005) to analyze the presence of stereotypes and preconceived ideas in participant exchanges, especially those done via a social network. The evidences generated by this analysis helped me self-reflect on, among other things, the relevance of teacher awareness regarding the insertion of pedagogical moments that allow students and professors to discuss and deconstruct stereotypes in interactions involving students from different cultures.